ICT Acceptance by University Professors: Knowledge, Attitude, and Practicality - Rivera-Laylle, Lucía Isabel; Fernández-Morales, Katiuska; Guzmán-Games, Francisco Javier; Eduardo-Pulido, Jesús (Revista Electrónica Educare, 2017)
The aim of this research is to analyze the acceptance of the Information and Communications Technology as tools to support the practice of teaching in private universities in Guatemala. It is a quantitative, descriptive, and transversal research study. It has been carried out with professors of degree and postgraduate courses in presential mode and with virtual environments of learning. A questionnaire was used to measure the “technology acceptance” (dimension) from three sub-dimensions: knowledge, attitude, and practicality. To analyze the data collected, we used descriptive statistics. The results were interpreted based on the “Technology Acceptance Model” (Davis, 1989; Venkatesh et al., 2003; Venkatesh y Bala, 2008). It was found that teachers are convinced of the usefulness of ICT, due to the variety of resources provided to develop school practices, tailored to the training needs and the needs arising from the knowledge society. However, professors “rarely” supervise the correct use of these tools by the student and “never” seek expert advice on the subject.